Deep learning-based hyperspectral microscopic imaging for cholangiocarcinoma detection and classification - Sravan Kumar S.; Sahoo O.P.; Mundada G.; Aala S.; Sudarsa D.; Pandey O.J.; Chinnadurai S.; Matoba O.; Muniraj I.; Deshpande A. (My University, 2025)
Cholangiocarcinoma is one of the rarest yet most aggressive cancers that has a low 5-year survival rate (2%-24%) and thus often requires an accurate and timely diagnosis. Hyperspectral Imaging (HSI) is a recently developed, promising spectroscopic-based non-invasive bioimaging technique that records a spatial image (x, y) together with wide spectral (λ) information. In this work, for the first time we propose to use a three-dimensional (3D)U-Net architecture for Hyperspectral microscopic imaging-based cholangiocarcinoma detection and classification. In addition to this architecture, we opted for a few preprocessing steps to achieve higher classification accuracy (CA) with minimal computational cost. Our results are compared with several standard unsupervised and supervised learning approaches to prove the efficacy of the proposed network and the preprocessing steps. For instance, we compared our results with state-of-the-art architectures, such as the Important-Aware Network (IANet), the Context Pyramid Fusion Network (CPFNet), and the semantic pixel-wise segmentation network (SegNet). We showed that our proposed architecture achieves an increased CA of 1.29% with the standard preprocessing step i.e., flat-field correction, and of 4.29% with our opted preprocessing steps. © 2024 Optica Publishing Group.